Peranan Laboratorium Terpadu Dalam Melahirkan Wirausaha Muda Melalui Program Pekan Kewirausahaa - Mail Hilian Batin; Iceu Sri Gustiana; Zulfikri (Forum Kerjasama Pendidikan Tinggi, 2022)
Role is an action performed by a person in an event. In this study, the role aimed at the Integrated Laboratory in carrying out the entrepreneurship week program. The presence of laboratories in universities is important as a place for students to experiment in the teaching and learning system. Material about Entrepreneurship is always taught to students, but only fixated on assignments but not yet of economic value. There is an entrepreneurship week program as a forum for students to be creative in selling their products to a wide audience and always evaluated by the laboratory if there are obstacles in the field. This type of research is field research with a qualitative approach. Primary and Secondary data are also needed as a complement to the perfection of the research. The results showed that integrated laboratories play a role in producing young entrepreneurs through the entrepreneurship week program, although there are still some obstacles that occur, but will always improve for future improvement.